Peran Motivasi Kerja dalam Meningkatkan Kinerja Guru di SMP Bina Siswa Laud Dendang - Anisa Aruan; Futhri Raudhatul Kabry; Maisa Muti Salsabilla Hsb; Mawaddah Tun’nisa; Zulfikar Lubis; Darmansah Darmansah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Work motivation is one of the key factors that contribute to improving teacher performance in education. This study aims to analyze the role of work motivation in improving teacher performance at SMP Bina Siswa, Laud Dendang. The method used in this study is a quantitative approach with data collection through questionnaires and interviews with teachers and school management. The results of the study indicate that good work motivation, both intrinsic and extrinsic, significantly affects teacher productivity and performance quality. Factors such as awards, recognition, a conducive work atmosphere, and support from school leaders have proven to be the main drivers in improving teacher work motivation. Thus, it is important for schools to continue to pay attention to the motivational needs of teachers in order to create a supportive work environment and improve the quality of education at the school.